Predictors of Mortality in Adults with Acute Kidney Injury Requiring Dialysis: A Cohort Analysis - Charles Kangitsi Kahindo; Olivier Mukuku; Vieux Momeme Mokoli; Ernest Kiswaya Sumaili; Stanis Okitotsho Wembonyama; Zacharie Kibendelwa Tsongo (International Journal of Nephrology)
Introduction. Acute kidney injury (AKI) requiring renal replacement therapy is accompanied by considerable mortality. This present study evaluated predictors of mortality at initiation of hemodialysis (HD) in AKI patients in Goma (in the Democratic Republic of the Congo (DRC)). Methods. A single-centre cohort survey evaluated the clinical profile and survival rates of AKI patients admitted to HD in the only HD centre in Goma, North Kivu province (DRC). Data were collected from patients who underwent HD for AKI. Patient demographics, comorbidities, clinical presentation, laboratory tests, and mortality were reviewed and analyzed. The survival study used the Kaplan–Meier curve. Predictors of mortality were evaluated using Cox regression. Results. Of the 131 eligible patients, the mean age was 43.69 ± 16.56 years (range: 18–90 years). Men represented 54.96% of the cohort. The overall HD mortality rate was 25.19% (n = 33). In multivariate analysis, independent predictors of mortality in AKI stage 3 patients admitted to HD were as follows: age ≥ 60 years (adjusted hazard ratio (AHR) = 15.89; 95% CI: 3.98–63.40; p<0.0001), traditional herbal medicine intake (AHR = 5.10; 95% CI: 2.10–12.38; p<0.0001), HIV infection (AHR = 5.55; 95% CI: 1.48–20.73; p=0.011), anemia (AHR = 9.57; 95% CI: 2.08–43.87; p=0.004), hyperkalemia (AHR = 6.23; 95% CI: 1.26–30.72; p=0.025), respiratory distress (AHR = 4.66; 95% CI: 2.07–10.50; p<0.0001), and coma (AHR = 11.39; 95% CI: 3.51–36.89; p<0.0001). Conclusion. Initiation of hemodialysis with AKI has improved survival in patients with different complications.